Malaria in the Post-Partum Period; a Prospective Cohort Study - Boel, Machteld E.; Rijken, Marcus J.; Leenstra, Tjalling; Pyae Phyo, Aung; Pimanpanarak, Mupawjay; Keereecharoen, Naw Lily; Proux, Stephane; Laochan, Natthapon; Imwong, Mallika; Singhasivanon, Pratap; White, Nicholas J.; McGready, Rose; et al. (PloS one, 2013)
Several studies have shown a prolonged or increased susceptibility to malaria in the post-partum period. A matched cohort study was conducted to evaluate prospectively the susceptibility to malaria of post-partum women in an area where P.falciparum and P.vivax are prevalent. In an area of low seasonal malaria transmission on the Thai-Myanmar border pregnant women attending antenatal clinics were matched to a non-pregnant, non-post-partum control and followed up prospectively until 12 weeks after delivery. Post-partum women (n = 744) experienced significantly less P.falciparum episodes than controls (hazard ratio (HR) 0.39 (95%CI 0.21-0.72) p = 0.003) but significantly more P.vivax (HR 1.34 (1.05-1.72) p = 0.018). The reduced risk of falciparum malaria was accounted for by reduced exposure, whereas a history of P.vivax infection during pregnancy was a strong risk factor for P.vivax in post-partum women (HR 13.98 (9.13-21.41), p<0.001). After controlling for effect modification by history of P.vivax, post-partum women were not more susceptible to P.vivax than controls (HR: 0.33 (0.21-0.51), p<0.001). Genotyping of pre-and post-partum infections [Formula in text] showed that each post-partum P.falciparum was a newly acquired infection. In this area of low seasonal malaria transmission post-partum women were less likely to develop falciparum malaria but more likely to develop vivax malaria than controls. This was explained by reduced risk of exposure and increased risk of relapse, respectively. There was no evidence for altered susceptibility to malaria in the post-partum period. The treatment of vivax malaria during and immediately after pregnancy needs to be improved.